Mesenchymal Stem Cells Protect Nucleus Pulposus Cells from Compression-Induced Apoptosis by Inhibiting the Mitochondrial Pathway - Sheng Chen; Lei Zhao; Xiangyu Deng; Deyao Shi; Fashuai Wu; Hang Liang; Donghua Huang; Zengwu Shao (Hindawi Limited, 2017)
Objective. Excessive apoptosis of nucleus pulposus cells (NPCs) induced by various stresses, including compression, contributes to the development of intervertebral disc degeneration (IVDD). Mesenchymal stem cells (MSCs) can benefit the regeneration of NPCs and delay IVDD, but the underlying molecular mechanism is poorly understood. This study aimed to evaluate the antiapoptosis effects of bone marrow-derived MSC (BMSC) on rat NPCs exposed to compression and investigate whether the mitochondrial pathway was involved. Methods. BMSCs and NPCs were cocultured in the compression apparatus at 1.0 MPa for 36 h. Cell viability, apoptosis, mitochondrial function, and the expression of apoptosis-related proteins were evaluated. Results. The results showed that coculturing with BMSCs increased the cell viability and reduced apoptosis of NPCs exposed to compression. Meanwhile, BMSCs could relieve the compression-induced mitochondrial damage of NPCs by decreasing reactive oxygen species level and maintaining mitochondrial membrane potential as well as mitochondrial integrity. Furthermore, coculturing with BMSCs suppressed the activated caspase-3 and activated caspase-9, decreased the expressions of cytosolic cytochrome c and Bax, and increased the expression of Bcl-2. Conclusions. Our results suggest that BMSCs can protect against compression-induced apoptosis of NPCs by inhibiting the mitochondrial pathway and thus enhance our understanding on the MSC-based therapy for IVDD.